DEVELOPMENT OF BUDDHIST EDUCATION TO PROPAGATE PEACEFULNESS IN THAI SOCIETY - Bhikkhu, Ven. Subinoy (The Journal of International Buddhist Studies College, 2019)
The main objectives of this article is to study Buddhist education and propagate peacefulness in Thai Society. Mostly, we can see East Asian peoples are following Mahayana Buddhism, South and Southeast Asian peoples are following Theravāda Buddhism. According to Theravāda Buddhism, there are three stages of Buddhist Education; Learning (Pariyatti), Practicing (Paṭipatti), and Realization (Paṭivedha). By developing this peacefulness activities in the Societies people can follows four principal strategies as; Physical Development, Behavioral Development, Mental Development and Intellectual Development. Buddhist Doctrinal teachings and its approach to solve on basis of Buddhist Doctrine which will provide main guidelines for developing our Mind, ending the suffering and the cycle of rebirths (saṁsāra).